IN SILICO STUDY OF Stachytarpheta jamaicensis ACTIVE COMPOUNDS AS ANTIBACTERIAL MATERIAL - Juliyatin Putri Utami; Sherli Diana; Rahmad Arifin (Dentino : Jurnal Kedokteran Gigi, 2022)
Background: Stachytarpheta jamaicensis is a wild plant from the Verbenanceae family that grows in tropical areas such as Indonesia. S. jamaecensis extract was proven to contain secondary metabolite compounds such as flavonoids, phenols, saponins, tannins and terpenoids. The active compound of S. jamaecensis can be used as a drug candidate in the medicine field, especially as an antibacterial compound. One of the first steps in predicting the effectiveness of these compounds can be done through in-Silico studies with molecular docking. Objective: This study aims to evaluate the interaction of active compound S. jamaecensis with bacterial proteins through an in silico study. Methods: Using in silico method with computational docking analysis on seven active compounds of S. jamaecensis namely apigenin, luteolin, chlorogenic acid, gamma butyric acid, dopamine, ipolamide and geraniol, as well as two antibacterial drugs (metronidazole and chlorhexidine) as comparisons bound with bacterial cell wall protein, namely Glucosamine-6-phosphate synthase (G1mS). Docking in silico uses Autodock Vina, which is integrated with PyRx 8.0 and visualized using Discovery Studio Visualizer v19.1.0.18287 (2019 version) with data presentation based on docking scores. Conclusion: The best binding affinity score has been the luteolin-G1mS complex with a binding affinity value of -10.8 kcal/mol and was the highest value compared to the comparison ligand binding and the binding of other active compounds of S. jamaecensis.